Creación de una familia tipográfica basada en elementos simbólicos de la cultura Jama - Coaque de la provincia de Esmeraldas. - Pesantez Mijas, Ana Cristina (2017)
Graphic design is intrusive in all the activities carried out by the human being, from the orientation we receive with the signs, to the development of packaging that we acquire in the supermarket, using iconic, linguistic and chromatic codes. The implicit creative process facilitates the interaction between sender and receiver, providing identity and information specifically for a specific target audience. The research is focused on the study of typography as a means of cultural and technological diffusion. The typography through the years has variations and aesthetic innovations that give us signs of funds and renewed forms, changing the appreciation of the text, it may seem modern, functional or cheerful. Choosing a typeface will depend a lot on the message we want to convey, a work that seems tiny, but it is very important. Currently the concept of typography has changed, it is not only about writing and reading, and it has created new typographical sources for any use, from reading to experimental, creating an interaction between the functional and the cultural, generating a relationship between the innovative and the aesthetic. Innovation within the field of graphic design allows to develop and manage typography as an integral part of culture. The present investigation arises from an analytical, synthetic and exploratory study based on the development of our theoretical framework, to obtain relevant information on the Jama-Coaque culture, it will comply with a semiotic analysis of its crafts, ceramic ornament and stamps that will contribute to the obtaining of elements and icons that with the characteristic creativity of the designers is intended to spread the development of a typographical family.